2009
DOI: 10.1088/0957-4484/20/43/434010
|View full text |Cite
|
Sign up to set email alerts
|

Long term investigations of carbon nanotube transistors encapsulated by atomic-layer-deposited Al2O3for sensor applications

Abstract: Single-walled carbon nanotube field-effect transistors (CNFETs) are promising functional structures in future micro- or nanoelectronic systems and sensor applications. Research on the fundamental device concepts includes the investigation of the conditions for stable long term CNFET operation. CNFET operation in ambient air leads to on-state current degradation and fluctuating signals due to the well-known sensitivity of the electronic properties of the CNT to many environmental condition changes. It is the go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 49 publications
5
62
0
Order By: Relevance
“…This source of flicker noise can be reduced in CNT-based sensors and transistors by encapsulating the CNTs in a ceramic coating in order to protect the CNTs from the outside environment. For example, it has been shown that encapsulating CNTs in 100 nm of atomic-layer-deposited aluminum oxide can increase device stability and decrease noise by almost an order of magnitude [26]. Similar results have been demonstrated for top-gated transistors where the ceramic encapsulation layer is used as the gate dielectric and passivation layer [27,28].…”
Section: Introductionsupporting
confidence: 55%
“…This source of flicker noise can be reduced in CNT-based sensors and transistors by encapsulating the CNTs in a ceramic coating in order to protect the CNTs from the outside environment. For example, it has been shown that encapsulating CNTs in 100 nm of atomic-layer-deposited aluminum oxide can increase device stability and decrease noise by almost an order of magnitude [26]. Similar results have been demonstrated for top-gated transistors where the ceramic encapsulation layer is used as the gate dielectric and passivation layer [27,28].…”
Section: Introductionsupporting
confidence: 55%
“…The ALD alumina is not removed at the source and drain contact regions. It is a good protection layer for the electrodes against unwanted environmental influences 8 and helps to increase device stability 12 . The ALD alumina layer is grown in a Picosun Sunale R-150B reactor at 150°C and in N 2 atmosphere at low pressure with water and trimethylaluminum (TMA) as source media for the film growth.…”
Section: Fabricationmentioning
confidence: 99%
“…Passivation of the devices with a protective layer, generally deposited by atomic layer deposition (ALD), ensures that the nanomaterials are not exposed to any further environmental and/or processing influences. 54 Identification of electrode-bridging nanomaterials is frequently performed by scanning electron microscopy at low acceleration voltages to minimize the risk of inducing any damage during visualization. Additional characterization can be carried out by AFM and electrical measurements.…”
Section: Site-and Type-selective Guided Assemblymentioning
confidence: 99%